Assessing the impact of mentorship on knowledge about and self-efficacy for neonatal resuscitation among nurses and midwives in Rwanda. (March 2021) - Nyiringango, Gerard; Kerr, Michael; Babenko-Mould, Yolanda; Kanazayire, Clementine; Ngabonzima, Anaclet
Abstract: In the first minute of life after birth, it is critical to effectively manage an infant's respiratory status. Given the critical nature of newborn airway management, it is vital that health professionals have the knowledge and confidence to engage in airway management procedures. Consequently, there has been a call for nurses and midwives to be prepared to skillfully enact neonatal resuscitation interventions when required, especially in low-resource environments, to help reduce neonatal death. The purpose of this study was to assess the impact of a mentorship program that involves an education component for neonatal resuscitation in the first minute after birth. The study examined changes to knowledge and self-efficacy of Rwandan nurses and midwives towards newborn airway care outcomes. A pre-/post-test, quasi-experimental study design was used to assess the changes in knowledge about and self-efficacy for neonatal resuscitation. Using a paired t -test, the results suggested that nurses' and midwives' knowledge and self-efficacy increased significantly, and participants' knowledge correlated positively to self-efficacy. Therefore, a mentorship program that supports professional development through education appears to be an effective strategy to enhance nurses' and midwives' knowledge about and self-efficacy for neonatal resuscitation and could eventually lead to neonatal practice improvements. Highlights: Birth asphyxia is highlighted as a major cause of neonatal mortality in developing countries of sub-Saharan Africa. mentorship contributes to the improvement of resuscitation skills among frontline health care providers in remote area of developing countries. Resuscitation practice-based mentorship program involved mentors facilitating mentees in health centers. The study findings indicate the positive change of mentees' knowledge and self-efficacy for neonatal resuscitation.